2022
DOI: 10.1017/s1368980022000568
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of zinc supplementation for prevention of childhood diarrhoea in Tanzania

Abstract: Objective: To assess the cost-effectiveness of prophylactic zinc supplementation for preventing diarrhoea in young children in Tanzania. Design: Cost-effectiveness analysis using decision-analytic modelling. Cost-effectiveness ratios were calculated as the incremental cost (2019 USD) per disability-adjusted life year (DALY) averted, from a societal perspective, and with a 3% discount rate applied to future outcomes. Sensitivity analyses were performed to test the robustness of results to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…Zinc supplementation was estimated to cost approximately $11 per child in a recent study. 5 Based on decision-analytic modeling, the authors reported that prophylactic zinc for 18 months did not appear to be cost-effective for the prevention of diarrhea in their setting. It is prudent that future studies address the above critical questions that determine the cost-effectiveness of 4, 9, or 11 months of zinc supplementation.…”
Section: Dear Editormentioning
confidence: 99%
“…Zinc supplementation was estimated to cost approximately $11 per child in a recent study. 5 Based on decision-analytic modeling, the authors reported that prophylactic zinc for 18 months did not appear to be cost-effective for the prevention of diarrhea in their setting. It is prudent that future studies address the above critical questions that determine the cost-effectiveness of 4, 9, or 11 months of zinc supplementation.…”
Section: Dear Editormentioning
confidence: 99%
“…21 Clinically, Zn deficiency affects various organs, particularly the gastrointestinal tract. 22 Reportedly, Zn supplementation can reduce the incidence of diarrheal episodes and diarrhea-induced morbidity, 23 and has a positive impact on maintaining the barrier function and homeostasis of intestinal epithelial cells. 24 Currently, there are 31 clinical trials of zinc supplements, alone or in combination with drugs, for the treatment of diseases involving diarrhoea, nutritional deficiencies, metabolic disorders, cancer, tuberculosis, etc.…”
Section: Introductionmentioning
confidence: 99%